Considerations for cardiac catheterization laboratory procedures during the COVID‐19 pandemic perspectives from the Society for Cardiovascular Angiography and Interventions Emerging Leader Mentorship (SCAI ELM) Members and Graduates. Issue 3 (21st April 2020) - Szerlip, Molly; Anwaruddin, Saif; Aronow, Herbert D.; Cohen, Mauricio G.; Daniels, Matthew J.; Dehghani, Payam; Drachman, Douglas E.; Elmariah, Sammy; Feldman, Dmitriy N.; Garcia, Santiago; Giri, Jay; Kaul, Prashant; et al.
Abstract: The novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), is highly infectious, carries significant morbidity and mortality, and has rapidly resulted in strained health care system and hospital resources. In addition to patient‐related care concerns in infected individuals, focus must also relate to diminishing community spread, protection of staff, case selection, and concentration of resources. The current document based on available data and consensus opinion addresses appropriate catheterization laboratory preparedness for treating these patients, including procedure‐room readiness to minimize external contamination, safe donning and doffing of personal protective equipment (PPE) to eliminate risk to staff, and staffing algorithms to minimize exposure and maximize team availability. Case selection and management of both emergent and urgent procedures are discussed in detail, including procedures that may be safely deferred or performed bedside.